Community Participation In Developing Cupak Village As A Tourist Destination In Jombang, East Java, Indonesia - Siti Mujanah; Candraningrat (Jurnal Bisnis dan Keuangan, 2023)
This research was conducted to utilize a model of community participation in the development Cupak Village as a Tourist Destination in Jombang, East Java, Indonesia. The approach used in this research is a qualitative approach, which describes the participation of the community in the development of a tourist village. The informants in this study were village officials, pokdarwis administrators, local youth organizations, community representatives and visitors. Information was taken through structured interviews. The study results show that developing a tourism village requires participation from various parties, including the community as the major actor, the local government, and stakeholders in charge of providing guidance. Likewise, the university's role took a significant place by providing Assistance in managing the tourism village while the role of SMEs is to provide special products that can be offered to visitors. The implication oif this study. This research aims to provide an overview of village communities in developing tourism villages by involving the community to participate.